ISLAMISASI DAN KAITANNYA DENGAN HUBUNGAN SERANTAU MALAYSIA - INDONESIA - Sulaiman, Mashita; Othman, Mohammad Redzuan (SEJARAH: Journal of the Department of History, 2017)
The process of Islamisation is often considered as the driving force in initiating social change in the Malay communities. It is undeniable that mutual influence plays a role in the relationship of the Muslim communities in Malaysia and Indonesia with regards to way of life, beliefs, and thoughts. The relationships between the two regions are enhanced through mutual communication among Islamic scholars, through trade and other activities. This paper traces the roles of Islamic da’wah in the history of relationship between the Malay communities in the region during the Islamic Malay sultanate around the 1800s until the early 1900s. This paper also analyses the process of Islamisation in Malaysia and Indonesia and the approaches taken by the Islamic activists in both countries during the Islamic revival of the 1970s until the 1990s. Activities by the Islamic movement and actions that had given impacts on the development of culture and changes in thinking are also discussed.